Inmigration news, xenophobic prejudices generator (2020)
The article exposes the links between the discourses that circulate socially, in this case the news from newspapers such as El Pais in Spain, where the contents stated therein facilitate the generation of prejudices and negative attitudes towards immigrants. It takes up the theoretical platform of social psychology, emphasizing the categories of prejudice, stereotypes in relation to critical discourse analysis of T. Van Dijk. In this sense, we conclude that media discourses help to shape and legitimize such hostile behavior or prejudice, revealing how the media has to do with the generation of cognitions or behaviors that are hostile to the different: in this case, the immigrant.